2020
DOI: 10.18291/njwls.122615
|View full text |Cite
|
Sign up to set email alerts
|

Youth Health and Safety Groups: Process Evaluation from an Intervention in Danish Supermarkets

Abstract: Young workers employed in temporary positions constitute a vast part of the employees in the Danish retail sector. The aim of the present study was to evaluate the implementation of an intervention to establish H&S groups for young workers in Danish supermarkets. The intervention aimed to include and involve the young workers in the management of their work environment and work conditions, and simultaneously to strengthen the organization’s ability to include them in the H&S management. The study was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Having the right assistive devices for the work tasks at hand may be important as well, granted that differences in physical workload have been reported between different technical assistive devices [ 61 , 62 ]. In relation to this, a recent Danish study among young supermarket workers suggested accessibility and functionality of the technical devices as places for improvement worth focusing on in the occupational health and safety work in the supermarkets [ 63 ]. However, it should be noted that the overall positive evidence for the prevention of MSD by use of technical devices is not convincing, which could be due to unsuccessful implementation [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Having the right assistive devices for the work tasks at hand may be important as well, granted that differences in physical workload have been reported between different technical assistive devices [ 61 , 62 ]. In relation to this, a recent Danish study among young supermarket workers suggested accessibility and functionality of the technical devices as places for improvement worth focusing on in the occupational health and safety work in the supermarkets [ 63 ]. However, it should be noted that the overall positive evidence for the prevention of MSD by use of technical devices is not convincing, which could be due to unsuccessful implementation [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%